Predicting students’ continued intention to use E-learning platform for college English study: the mediating effect of E-satisfaction and habit - Deng, Ping; Chen, Bing; Wang, Li (Frontiers in Psychology, 2023)
The wide application of modern information technology in the field of education not only breaks time and place constraints to disseminate knowledge quickly but also further broadens the diversity and depth of learning mode and content. E-learning platform, as an information technological innovation, is widely used to learn college English. However, few studies have explored the motivations for students’ e-satisfaction and continued intention towards using it for college English study. Based on the extended Unified Theory of Acceptance and Use of Technology (UTAUT2), this study identifies the influencing factors for the continued usage intention and tests the mediating role of e-satisfaction and habit. The partial least squares structural equation modelling (PLS-SEM) was applied to analyze the data. Results show that performance expectancy, learning value, hedonic motivation and habit positively affects students’ continued usage intention, e-satisfaction positively mediates the relationship between the antecedents and continued usage intention, and habit positively mediates the relationship between e-satisfaction and continued usage intention. The research provides guidelines for the successful implementation of e-learning platform for college English study and key references for improvement of students’ engagement and satisfaction experience with using e-learning platform for college English study.